A 2, 2′-bipyridine coordination complex of [ICl2]+. Issue 34 (1st December 2014) - Shaw, Andrew J. M.; Corbo, Robert; Wilson, David J. D.; Dutton, Jason L.
Abstract : A straightforward synthesis of a new type of iodine(iii ) complex is presented – an N ′ N chelated [ICl2 ] + cation. Abstract : The formation of a new class of I(iii ) compound is reported; an N, N ′ chelated iodine cation ([bpy-ICl2 ] + ; bpy = 2, 2′-bipyridine). The complex is obtained as an [ICl4 ] − salt and is formed via simple reaction of bpy with ICl3 . The compound is relatively unstable, but may be stored as a solid and is shown to be competent in the oxidative chlorination of Au(i )-NHC complexes.